Pengaruh Financial Compensation , Career Development, dan Motivation Terhadap Employee Performance Pada Karyawan Minimarket di DKI Jakarta - Jumitasari, Jumitasari; Seto, Samudro (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The minimarket retail sector is a crucial part of the economy because it directly relates to customer service. However, employee performance remains a challenge that companies need to address. This study aims to analyze the influence of financial compensation, career development, and motivation on employee performance among minimarket employees in Jakarta. This study used a quantitative approach with a survey method. Data were collected through a questionnaire using a five-point Likert scale from 150 respondents selected using a purposive sampling technique, namely employees who had worked for at least six months. Data analysis was performed using multiple linear regression with the help of SPSS software after meeting the classical assumption test. The results showed that financial compensation, career development, and motivation simultaneously had a positive and significant effect on employee performance. Partially, these three variables were also proven to have a positive and significant influence, with financial compensation being the most dominant variable. These findings indicate that providing fair compensation, providing career development opportunities, and good work motivation can collectively improve employee performance in the minimarket sector.